Small-world network organization of functional connectivity of EEG gamma oscillation during emotion-related processing - Manfang Ma; Yingjie Li; Zhenzhu Xu; Yingying Tang; Jijun Wang (2012 5th International Conference on Biomedical Engineering and Informatics, 2012)
In this study we investigated whether functional brain networks are variously organized during different emotional processing. Electroencephalography (EEG) activities were recorded in 27 healthy subjects when they performed a spatial search task for facial expressions. Correlations between all possible pairs of electrodes placed over the scalp were determined by coherence and the coherence matrices were calculated within gamma frequency bands, i.e. low gamma for 30-50Hz and high gamma for 50-80Hz, respectively. Graph theoretical analysis was applied to these matrices using two measures: the clustering coefficient and the characteristic path length. We found the network organization of the EEG gamma oscillation during emotion processing showed characteristic of small-world networks; this type of organization is slightly but significantly more evident during negative emotional processing. We concluded that negative emotion processing showed more effective and optimal network organization for information processing than positive.